Green chemistry of polymers - Pińkowska, H. (Polimery, 2022)
The article is a review of the newest literature data (159 references) concerning the application of the rules of green and sustainable chemistry in chemistry of polymers. The processes (being in agreement with these rules) of manufacturing of intermediate products for polymers syntheses, coming from oil or renewable resources, as well as the polymerization carried out in the presence of metallocene or enzymatic catalysts were described. Alternate media of polymerization reactions, such as supercritical carbon dioxide, ionic liquids and water, were characterized. Special attention has been paid to biodegradable polymers, feedstock recycling and energy recovery from polymeric materials used, especially in the presence of supercritical liquids.